Development of 4D printed smart fresnel lenses: dynamic photochromic and UV-blocking capabilities via vat photopolymerization - Bilal Bukhari; Murad Ali; Rashid K. Abu Al-Rub; Haider Butt (Light: Advanced Manufacturing)
Advancements in additive manufacturing (AM) are revolutionizing 3D part production, making 3D printing crucial for creating optical devices like lenses and waveguides. This study employs vat photopolymerization (VPP) to fabricate adaptive 4D printed smart Fresnel lenses with photochromic properties using digital light processing (DLP). These lenses are fabricated with precise optical performance and geometric dimensions. Photochromic powders enable dynamic color changes upon UV exposure. The lenses were optically evaluated in both inactive and active states, demonstrating excellent UV and blue light blocking when inactive. Upon UV activation, the lenses darken and absorb parts of the visible light spectrum, with the degree of absorption and color change dependent on the photochromic material and its concentration. The lenses show minimal focal length errors, maintaining high precision and UV responsiveness even at low concentrations. This research highlights the lenses’ precision, UV responsiveness, blue light filtering capabilities, and stability after multiple UV exposure cycles. These findings underscore the potential of 4D printing in developing smart optical devices tailored for applications that demand dynamic light modulation and UV filtering, highlighting a combination of innovative manufacturing techniques and functional optics.